Company Support for Environmental Sustainability: How Does CSR Defend Environmental Sustainability in Indonesia? - Henggar Budi Prasetyo (Unnes Law Journal, 2019)
This paper is intended to analyze how the implementation of the survey and identification as a basis for channeling funds to the Community Development Program of PTPN IX and how to account for the distribution of funds Environment Development Program at PTPN IX? This study classified the type of qualitative empirical juridical approach with descriptive-analytic specifications. The type of data used are primary data. Data obtained through interview and document study. The data obtained and analyzed by inductively to be concluded. The results obtained showed that PTPN IX in the implementation of the survey and identification of the distribution of the Community Development Program funds to repair roads in the village Sukomangli 2014 using the method of submission of the proposal by the community. The public in this case is positioned as the subject and object of the program. While, PTPN IX positioned as a facilitator realization of targets set out in the proposal. On the distribution of aid funds are PTPN IX compiling reports and the use of funds for implementing dipertanggungjawakan by the Board of Directors to the AGM. The report was approved by the AGM that the Board of Directors in this regard has gained release and discharge of responsibility for the implementation of environmental Development Program in fiscal year 2014.